Eat or you are eaten': prostitution as a metaphor in selected Ngugi's literary works (2010)
This paper examines the phenomenon of prostitution as treated in selected literary works of a renowned East African literary scholar, Ngugi wa Thiong’O. The paper identifies two perspectives from which Ngugi presents the phenomenon of prostitution: first as a product of exploitative socio-political and economic realities of post-colonial Kenyan society, and second, as a metaphoric representation of the nature of the relationship existing between African leaders (neocolonialists) and the people they lead on one hand, and on the other, the relationship between the African elite and the Western world. Ngugi then criticizes the development processes adopted by African leaders, which continue to tie them to the dictates of the West for solution to the continent’s development challenges. Ngugi merges art and ideology and advocates alternative political and economic ideology that promotes sustainable socio-cultural and economic wellbeing of the generality of the African people. The paper therefore concludes that African literary scholars have continued to raise issues that are of anthropological concern. The phenomenon of prostitution is a social problem that bothers on human behavior as it relates to human survival. But Ngugi goes beyond this level of discourse to provide alternative way of viewing prostitution with its underpinning on the meanings behind reflected human conduct.